Dihydroartemisinin Ameliorates Learning and Memory in Alzheimer’s Disease Through Promoting Autophagosome-Lysosome Fusion and Autolysosomal Degradation for Aβ Clearance - Zhao, Yueyang; Long, Zhimin; Ding, Ya; Jiang, Tingting; Liu, Jiajun; Li, Yimin; Liu, Yuanjie; Peng, Xuehua; Wang, Kejian; Feng, Min; He, Guiqiong (Frontiers in Aging Neuroscience, 2020)
Dihydroartemisinin (DHA) is an active metabolite of sesquiterpene trioxane lactone extracted from Artemisia annua, which is used to treat malaria worldwide. DHA can activate autophagy, which is the main mechanism to remove the damaged cell components and recover the harmful or useless substances from eukaryotic cells, and maintain the cell viability through autophagy lysosomal degradation system. Autophagy activation and autophagy flux correction are playing an important neuroprotective role in the central nervous system, as they accelerate the removal of toxic protein aggregates intracellularly and extracellularly to prevent neurodegenerative processes, such as Alzheimer's disease (AD). In this study, we explored whether this mechanism can mediate the neuroprotective effect of DHA on AD model in vitro and in vivo. Three months of DHA treatment improved the memory and cognitive impairment, reduced the deposition of amyloid β plaque, reduced the levels of Aβ40 and Aβ42, and ameliorated excessive neuron apoptosis in APP/PS1 mice brain. In addition, DHA treatment increased the level of LC3 II/I and decreased the expression of p62. After Bafilomycin A1 and Chloroquine blocked the fusion of autophagy and lysosome, as well as the degradation of ALs, DHA treatment increased the level of LC3 II/I and decreased the expression of p62. These results suggest that DHA treatment can correct autophagic flux, improve autophagy dysfunction, inhibit abnormal death of neurons, promote the clearance of Aβ fibrils, and have a multi-target effect on the neuropathological process, memory and cognitive deficits of AD.